PIONEERING COSMOPOLITAN PANORAMA OF FINANCIAL FRAUD: A BIBLIOMETRIC ANALYSIS - Nair, Arjun J; Saluja, Shefali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The research aims to provide a comprehensive bibliometric analysis of financial fraud scholarship from 1976 to May 2022. By examining publication trends, key contributors, and thematic developments, it seeks to shed light on the evolution and current state of financial fraud research. This study aspires to identify significant journals, authors, institutions, and collaborative networks while highlighting research gaps and emerging areas within the field. It aims at informing future study and practical applications in the area of fraud prevention and control, with actionable insights towards both researchers and practitioners alike. Bibliometric study was used to extract and to analyze peer-reviewed publications into the Scopus database on financial fraud. The data were categorized according to the year of publication, the country, the journal, and the author and the organization for one to assess trends and productivity about the field. Metrics such as citation counts, H-Index scores, frequency, and percentages were computed to assess research impact. Collaborative networks and thematic developments were mapped using co-authorship and keyword analyses. The results of the analysis show that financial fraud research publications have been constantly increasing since 1976, indicating a growing academic and practical interest in the area. The Journal of Financial Crime is the leading publication venue, which reflects its importance in the advancement of the field, with an impact score of 1.5 and an H-Index of 26 as of June 2022. However, the study identifies gaps in the literature, characterized by limited thematic ideologies and keywords, as well as sparse international collaborative networks. This lack of global research connectivity opens up opportunities for creating collaborations to address the intrinsically global nature of financial fraud. Bibliometric data also show annual growth patterns and key performance indicators, which again points to the importance of focused research on emerging fraud threats. The implications of this research are many. It gives academics a clear understanding of underexplored themes and regions in financial fraud studies and guides the direction of further inquiries. For policymakers and practitioners, the study provides a foundation for developing targeted interventions and collaborative strategies to combat fraud on a global scale. The findings further encourage journal publishers and funding bodies to focus on financial fraud research, given its profound societal and economic impacts. Furthermore, the identification of gaps in international collaboration underscores the need for multidisciplinary and transnational research initiatives to tackle financial fraud effectively. This study represents a novel contribution to the financial fraud research domain by presenting one of the few bibliometric analyses covering over four decades of scholarly work.